Photocatalytic Stoichiometric Oxidant-Free Synthesis of Linear Unsaturated Ketones from 1,2-Disubstituted Cyclopropanols - Laktsevich-Iskryk, Marharyta V.; Krech, Anastasiya V.; Zhabinskii, Vladimir N.; Khripach, Vladimir A.; Hurski, Alaksiej L. (Synthesis, 2020)
A one-step catalytic oxidant-free synthesis of unsaturated ketones from 1,2-disubstituted cyclopropanols is reported. Previously for this transformation, only two- and three-step protocols have been developed. The reaction proceeds under irradiation with visible light in the presence of catalytic amounts of both an acridinium photocatalyst and a cobaloxime complex. 2-Aryl-substituted cyclopropanols react giving α,β-unsaturated ketones, while dehydrogenative ring opening of 2-alkyl-substituted substrates affords mixtures of α,β- and β,γ-enones. The reaction starts with one-electron oxidation of a cyclopropanol to cyclopropyloxy radical, presumably, by the photoexcited acridinium catalyst. We also found that Co(dmgBF2)2(MeCN)2 complex under an air atmosphere and irradiation with blue LEDs or upon heating can serve as a hydroxycyclopropane oxidant.
Keywords: Key words; cyclopropanols; photochemistry; enones; cobaloxime; ring opening